The evolution of civil society in the history of political and legal thought. (Journal of actual problems of jurisprudence, 2016)
In the modern era had a steady development of the law of the nature relationship between the state and civil society,beginning with the question of becoming a legal state as a new form of interaction between civil society and the rule of law. Functioning of the institutions of civil society as the main conditions for the development of the legal state acquired a qualitatively new character, strengthening research that led to these relationships, reflecting the strategic task of law, seeking to perceive civil society as an ally and partner.
Keywords: identity; civil society; the evolution of the model; the concept of the state